A Question of Managerial Legitimacy - McNulty, Marian S. (Academy of Management Journal, 1975)
There is a reciprocity between the corporations and society which, through the divorce of ownership from control, has been left in an ambiguous state. The inheritor of responsibilities and privileges on the corporate side is management, as an elite responsible to employees. Therefore, managerial legitimacy is democratic rather than autocratic.